A rare association of caecal volvulus and intestinal malrotation causing an acute abdomen: Case report. (May 2021) - Chaker, Youssef; Ouadi, Yacine; Ben Mahmoud, Ahmed; Haddad, Anis; Magherbi, Houcine; Kacem, Montasser
Abstract: Introduction: and importance: Caecal volvulus represents 30% of colonic volvulus. It happens due to torsion or hyperflexion of a hypermobile caecum. Usually it is secondary to an axial rotation of the caecum and the ileum around the mesentery. On the other hand Intestinal malrotation occurs due to incomplete or faulty rotation and fixation of the gut during fetal life. The occurrence of these two anomalies together is scarse which makes this case report interesting. Case presentation: A 75 year old man with medical history of terminal kidney failure, presented to the emergency room with an intestinal obstruction syndrome. On examination the patient had a distended abdomen with tenderness in the left upper quadrant. Biology found an important biological inflammatory syndrome with hyperleukocytosis and elevated CRP. Plain X-ray of the abdomen in erect posture showed an air fluid colonic level in the left hypochondrium. CT scan showed signs of caecal volvulus with intestinal malrotation. A brief reanimation and nasogastric aspiration couldn't solve the problem therefore emergency laparotomy was needed ileocaecal resection was performed associated with LADD's procedure in order to treat both anomalies and prevent further gut volvulus. Clinical discussion: Despite it's rareness, caecul volvulus represents the second cause of large bowel volvulus just behind sigmoid volvulus. Intestinal malrotation in adults subjects is estimated to occur in 0.2–0.5%.The uniqueness of our case is that these two anomalies were associated in such a way that it made both the diagnosis and the therapy even more difficult. Abdominal CT has become mandatory for pre-operative diagnosis of intestinal volvulus. Surgery is the gold standard treatment for caecal volvulus. The usual options are manual detorsion, carcopexy, caecostomy and colectomy. Conclusion: This case reports a rare association of a caecum volvulus with intestinal malrotation that emphasis the place of modern technologies such as CT scan in order to achieve correct preoperative diagnosis. We also describe our approach to this uncommon surgical emergency in order to provide an efficient treatement. Highlights: Caecal volvulus associated with intestinal malrotation is rare. CT scan is mandatory for preoperative diagnosis of caecal volvulus. Surgery is the only permanent solution. Association of procedures for the caecal volvulus and the intestinal malrotation is the only prevention from recurrence.